Conformity assessment with structural strength requirements of mechanical polycentric prosthetic knee used for amputee rehabilitation. Issue 7 (19th May 2023) - Mohanty, Rajesh Kumar; Mohanty, R C; Sabut, Sukanta; Pandey, Mukundjee
Abstract: Prosthetic restoration is an important component of amputee rehabilitation which may be subjected to a static load of nearly five times of amputees' body weight and is continuously administered to cyclic or fatigue loads during its function. This study presents a structural strength analysis of polycentric mechanical prosthetic knee commonly used in National Institutes in India by finite element simulation and its experimental validation. Static and fatigue analyses have been performed to ensure its structural integrity as per the ISO 10328:2006 standard. Accurate dimensioning of knee components have been obtained using coordinate measuring machine and the 3 D CAD model has been generated by CATIA V5 from the 2 D geometry. The model is imported to the ANSYS 20.1 workbench to study stress distribution in the knee for ensuring its safety performance. The selection of reference planes, application of calculated loads, and position of load line have been done as per the ISO test procedure. Static and cyclic loadings of 4130 N and 1230 N are applied at the top and the bottom plate is given with translational constraints to limit its movement in any direction. Results indicate that the prosthetic knee model is moderately strong enough to outstrip the static strength test. However, the calculated strain and predicted fatigue life during the cyclic test suggest that this knee unit has poor fatigue strength. Validation results with an average error percentage of 3.44 and 10 show higher reliability based on previous study results and experimental tests, respectively.